2022
DOI: 10.1111/plb.13391
|View full text |Cite
|
Sign up to set email alerts
|

Satellite data track spatial and temporal declines in European beech forest canopy characteristics associated with intense drought events in the Rhön Biosphere Reserve, central Germany

Abstract: The increasing intensity and frequency of droughts under climate change demands effective ways to monitor drought impacts. We sought to determine how different satellite remote sensing sources influence our ability to identify temporal and spatial impacts on European beech forest canopy health during intense drought events.• Imagery from three satellite series (MODIS, Landsat and Sentinel-2) was used to observe changes in canopy health during the intense droughts of 2003 and 2018 in the Rh€ on Biosphere Reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
(160 reference statements)
0
17
0
Order By: Relevance
“…However, in this paper, the annual NDVI was prepared as the median of the maximum monthly NDVI values of the growing season for the year in question. Similar approach was used in, for example, Romania (Pr av alie et al, 2022) and Germany (West et al, 2022). The rationale behind using median is that it represents the situation of the vegetation over the whole growing season better than, for example, sole maximum value.…”
Section: Modis-ndvi Vegetation Indexmentioning
confidence: 99%
“…However, in this paper, the annual NDVI was prepared as the median of the maximum monthly NDVI values of the growing season for the year in question. Similar approach was used in, for example, Romania (Pr av alie et al, 2022) and Germany (West et al, 2022). The rationale behind using median is that it represents the situation of the vegetation over the whole growing season better than, for example, sole maximum value.…”
Section: Modis-ndvi Vegetation Indexmentioning
confidence: 99%
“…The authors analysed the pan-European ICP Forest crown defoliation dataset for the last 25 years and found species-specific increasing trends in mortality rates for major coniferous, major broadleaved and a pooled dataset of minor European timber species related to decreasing soil moisture. West et al (2022) observed the development of extreme droughts, such as the 2018 event, on satellite-derived canopy vitality by assessing the normalized vegetation index (NDVI), which quantifies reductions in vegetation greenness. According to their results from a typical beech forest in central Germany, canopy responses lagged behind the onset of the 2018 drought by up to 2 months, showing peaks in August and September.…”
Section: Effects Of the 2018 Drought On Forest Healthmentioning
confidence: 99%
“…West et al . (2022) observed the development of extreme droughts, such as the 2018 event, on satellite‐derived canopy vitality by assessing the normalized vegetation index (NDVI), which quantifies reductions in vegetation greenness. According to their results from a typical beech forest in central Germany, canopy responses lagged behind the onset of the 2018 drought by up to 2 months, showing peaks in August and September.…”
Section: Effects Of the 2018 Drought On Forest Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…This special issue, edited by Schuldt & Ruehr (2022), evaluates tree and forest responses to the 2018 European hot drought, one of the most severe droughts ever recorded in Central Europe. It illustrates and differentiates viewpoints across scales, from acclimation potential and regulatory mechanisms at the leaf level (Kunert et al 2021;Weithmann et al 2021;McAdam et al 2022;Petrik et al 2022), embolism and wood formation plasticity (Petruzzellis et al 2021;Larysch et al 2022;Meyer et al 2022), impacts of different management regimes (Bose et al 2021;Meyer et al 2022) and species interaction effects in mixtures Santamarina et al 2022), to results from remote sensing West et al 2022).…”
mentioning
confidence: 99%